We'd Go Well Together: A Critical Race Analysis of Marijuana Legalization and Expungement in the United States. (3rd September 2021) - Crawford, Nyron N.
Abstract: In the U.S., many state and local governments have either legalized or decriminalized small quantities of marijuana for recreational or medicinal use. Reforming these laws has had significant public support, with reformers arguing that dissolving prohibitions on use as a policy remedy, or recompense, for the economic and human cost born by African American communities in the so-called "War on Drugs." However, we do not yet know what explains the shift in support for allowance, or, more specifically, what has widened the policy window for legislative reform across the country. Using the analytic framework of Critical Race Theory (CRT), specifically, Bell's (1980) notion of issue convergence, this paper highlights how this specific policy change continues to reproduce inequality in the maintenance of racialized interests in terms of who benefits and is burdened by reform. It concludes by recommending additional legislative action, such as automatic expungements for certain marijuana-related crimes, a legal remedy that can limit the collateral consequences experienced by those with criminal records.